2011
DOI: 10.1002/adma.201003974
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Programmable Magnetoresistance in Multifunctional Organic‐Based Spin Valve Devices

Abstract: Information and communication technology (ICT) is now calling for solutions enabling lower power consumption, further miniaturization, and multifunctionality requiring the development of new device concepts and new materials. [ 1 ] One of the most fertile approaches to meet such demands is spintronics, which is now facing the challenge of evolving from the fi rst generation of devices that led to a revolution in information storage [ 2 ] (giant magnetoresistance readheads), to devices that exhibit multioperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 26 publications
(31 reference statements)
2
95
2
Order By: Relevance
“…The impurities might be metal atoms, which serve as donors, or O 2 molecules, which serve as acceptors. The presence of highdensity impurities in the OSVs is further supported by the accompanying memory effect 22 caused by charge storage, as in the electroformed inorganic structures 20,21 . Such memory effects are not expected from the organic diode of Fig.…”
Section: Forward Biasmentioning
confidence: 90%
“…The impurities might be metal atoms, which serve as donors, or O 2 molecules, which serve as acceptors. The presence of highdensity impurities in the OSVs is further supported by the accompanying memory effect 22 caused by charge storage, as in the electroformed inorganic structures 20,21 . Such memory effects are not expected from the organic diode of Fig.…”
Section: Forward Biasmentioning
confidence: 90%
“…First, the temperature dependence of the resistance of most organic SVs is weak [7][8][9][10][11][12][13][14][15][16][17] , resembling more the behaviour of a tunnel junction than the temperature-activated transport typical of organic films 21 . Therefore, the question rises whether the SVs are actually probing the properties of the organics, or they are prone to artifacts coming from the interpenetration of the top metal contact into the organic layer.…”
mentioning
confidence: 99%
“…In addition to the long spin lifetimes, it has been noticed that the combination of molecules and FM offers other intriguing possibilities for spintronics. For instance, devices with novel functionalities have been demonstrated by exploiting properties of the semiconducting molecules, such as light emission 16 , electrical bistability 17 and hot electron filtering 18 . Furthermore, reaction at a molecule/FM interface can result in interfacial states 19,20 with modified energetics and spin polarization.…”
mentioning
confidence: 99%
“…Thus, the mechanism behind the positive spin-1/2 ELDMR in rubrene-doped Alq 3 devices is the same as the mechanism behind the positive spin-1/2 PLDMR in MEH-PPV films, i.e., enhanced annihilation of TE-polaron pairs (TPQ) that reduces the TE and polaron populations under resonance conditions, and in turn reduces the quenching of SEs by TEs and polarons. Higher j produces more polarons on Alq 3 moledcules, which enhances the 42 TPQ effects, including ELDMR.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that a strong spin valve effect of ~22% was achieved in a tris(8-hydroxyquinolinato) aluminium (Alq 3 )-based device [42].…”
Section: Other Applicationsmentioning
confidence: 99%